The nature of Evidence Rules in Administrative Case - Al-Ubaidy, Lec. Saif Alaa Hussein (The college of law and political science journal, 2023)
The idea of this research revolves around The nature of evidence rules in Administrative Case in that the rules of evidence are the means by which the right holder reaches to establish evidence of the establishment of this right and presents it to the judiciary to reach his right. A right without proof is considered non-existent from a practical point of view, and here the element of the claimed right and the element of the law must be proven, which is legal rule that determines this right. And the object of proof does not respond to the claimed right, but rather responds to the legal fact that establishes this right, and that the importance of proof is not limited to achieving a special interest for the parties to the litigation, but rather aims to achieve to public interest.